Modeling and analysis of semiconductor manufacturing systems with degraded behavior using Petri nets and siphons. - MuDer Jeng (IEEE Transactions on robotics and automation)
Degraded behavior, such as reworks, failures, and maintenance, of a semiconductor manufacturing system (SMS) is not negligible in practice. When modeled by Petri nets, degraded behavior may be represented as initially unmarked elementary circuits, interpreted as local processing cycles. We extend the class of nets we presented previously (1997) into the class of RCN* merged nets that model SMSs with such cycles. To model an SMS, we first describe the behavior of each resource type using a state-machine module, called RCN. Any RCN can be constructed as a connection of acyclic subnets called blocks, where one of them denotes the normal behavior of the resource type and the others denote its degraded behavior. Next, an RCN* merged net for the entire system is built by fusing all modules, conforming to three constraints, along their common transition subnets, which represent their synchronization. In the analysis of RCN* merged nets, we prove that their liveness and reversibility depend on the absence of unmarked siphons, which are structural objects that mixed integer programming can check rapidly. Examples are given to illustrate the proposed approach